2021
DOI: 10.3390/ma14030649
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restorative Material on Mechanical Response of Provisional Endocrowns: A 3D—FEA Study

Abstract: The goal of this study was to evaluate the stress distribution in an endocrown restoration according to different provisional restorative materials. An endodontically treated maxillary molar model was selected for conducting the finite element analysis (FEA), with a determined amount of dental remnant of 1.5 mm. The model was imported to the analysis software (ANSYS 19.2, ANSYS Inc., Houston, TX, USA) in STEP format. All contacts were considered perfectly bonded. The mechanical properties of each structure wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The explanation for the worst biomechanical behavior for the Young design is because the cusps of posterior teeth substantial increased the bending and flexural loads during functional and parafunctional occlusal movements. These applied loads can theoretically generate a horizontal force component which tends to open up the principal sulcus space increasing the tensile stress concentration and subsequent creating cracks at the bottom of the fissure [22,23]. The present study corroborates with this statement since the numerical simulation showed an increased stress magnitude when the Young anatomy was used.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The explanation for the worst biomechanical behavior for the Young design is because the cusps of posterior teeth substantial increased the bending and flexural loads during functional and parafunctional occlusal movements. These applied loads can theoretically generate a horizontal force component which tends to open up the principal sulcus space increasing the tensile stress concentration and subsequent creating cracks at the bottom of the fissure [22,23]. The present study corroborates with this statement since the numerical simulation showed an increased stress magnitude when the Young anatomy was used.…”
Section: Discussionsupporting
confidence: 87%
“…A previous finite element study suggest that the cusp angle can modify the loads incidence for provisional endocrowns restored molars [23]. The same indication can be performed for the present study considering only the fracture load and stress concentration for acrylic resin crowns.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, the digital process provides not only upgrades in the available dental materials but also a more precise final restoration [3]. The major advantage of CAD/CAM provisional materials is its industrial manufacture, reducing defect incorporation in the material bulk in comparison with the manual technique [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The interfaces in all models were considered perfectly bonded. Table 1 [ 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] summarizes the mechanical properties (elastic modulus and Poisson ratio) used for the mechanical analysis. An average of 156,252 nodes and 128,242 tetrahedral, ten nodes, elements were used for the meshing process after a convergence test with a 10% degree of freedom of the converged value and mesh size, based on the maximum principal stress (MPS) results.…”
Section: Methodsmentioning
confidence: 99%